PENINGKATAN MOTIVASI BELAJAR SKI MATERI PERISTIWA AKHIR HAYAT RASULULLAH MELALUI STRATEGI TEAM QUIZ PADA SISWA KELAS VA MINU BERBEK WARU SIDOARJO - Fitriyanah, Nur (Journal Of Islamic Elementary School (JIES), 2017)
This research is motivated by the low learning motivation of class VA students in SKI subjects on the subject of the Prophet’s end of life events. This happens because of several factors, namely, at the beginning of learning, many students are not ready to take part in learning activities. In addition, SKI subject teachers do not use innovative learning methods or strategies in delivering material, so that many students feel bored, bored and sleepy during the learning process. This study aims to determine the application of the team quiz strategy in increasing the motivation to learn SKI on the subject of the Prophet’s End of Life Events in the VA MINU Berbek, Waru Sidoarjo class and to find out the increase in the motivation to learn SKI in the Prophet’s End of Life Events material after using the team quiz strategy in the VA MINU Berbek class. , Waru Sidoarjo. This type of research is classroom action research which is carried out in two cycles. This classroom action research uses Kurt Lewin’s model, where in one cycle there are four main steps, including planning, implementation, observation or observation and reflection. The data collection techniques used are interviews, observation, questionnaires and documentation. The results obtained from this study indicate that the motivation of class VA students in learning SKI has increased. The average value of students’ learning motivation in the pre-cycle was 61.86 and then increased to 74.34 in the first cycle, and in the second cycle it reached 84.04. The percentage of students’ complete learning motivation in the pre-cycle is 4.34%, and then in the first cycle it increases to 43.47% and in the second cycle it reaches 82.6%.